Investigation on the effect of 238U replacement with 232Th in small modular reactor (SMR) fuel matrix - Uguru, E.H.; Sani, S.F. A.; Khandaker, Mayeen Uddin *; Rabir, M. H. (Elsevier, 2020)
Effect of 238U replacement with 232Th in small modular reactor fuel matrix was studied. Four different 235U enrichment levels (10, 13.8, 16.5 and 19.8 wt%) were used in a pairwise manner for UO2 and (ThO2 + 235U) fuels. The calculation was performed using Monte Carlo N-particle code integrated with CINDER90 for burn-up calculations in a homogeneous fuel assembly. The results show that enrichment level <17 wt% for thorium fuel produced virtually no plutonium isotopes but became visible only at 19.8 wt% enrichment. The number of neutrons produced per fission () for ThO2 + 235U was less than that of UO2 because its averaged contribution from 235U and 233U was smaller compared to the similar contribution from 239Pu, 241Pu and 235U. Large amount of 239Pu and actinides were produced from UO2 fuel due to the impact of 238U. The reactivity of thorium at the beginning of cycle (BOC) was smaller compared to uranium but higher at end of cycle (EOC) resulting to higher excess reactivity in all thorium fuel. Production of little plutonium isotopes by thorium fuel suggests that it would make a good proliferation resistance fuel and could be used in any W-SMR to incinerate stockpiled plutonium.